2010
DOI: 10.1093/cercor/bhq038
|View full text |Cite
|
Sign up to set email alerts
|

It Was Not MY Fault: Event-Related Brain Potentials in Active and Observational Learning from Feedback

Abstract: Performance feedback during learning is accompanied by a negative event-related potentials (ERP) component, the feedback-related negativity (FRN), which codes a reward prediction error. An open issue relates to the coding of feedback stimuli in observational learning. The present study aimed to determine differences in the neural processing of feedback in active and observational learners in a between-subjects design. By choosing between different stimuli, 15 active learners could learn a rule determining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 29 publications
12
65
1
Order By: Relevance
“…With regard to the role of agency in performance monitoring, we found a larger FRN for one's own than for observed performance feedback. This effect corroborates previous results (Bellebaum, et al, 2010;Fukushima & Hiraki, 2009;Leng & Zhou, 2010;Yu & Zhou, 2006). As proposed by Bellebaum et al (2010), it is likely that such agency-related enhancement results from the higher personal relevance of feedback about one's own performance, and is consistent with a greater importance of such feedback in terms of subsequent behavioral adjustment (Holroyd & Coles, 2002;Ridderinkhof, Ullsperger, Crone, & Nieuwenhuis, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With regard to the role of agency in performance monitoring, we found a larger FRN for one's own than for observed performance feedback. This effect corroborates previous results (Bellebaum, et al, 2010;Fukushima & Hiraki, 2009;Leng & Zhou, 2010;Yu & Zhou, 2006). As proposed by Bellebaum et al (2010), it is likely that such agency-related enhancement results from the higher personal relevance of feedback about one's own performance, and is consistent with a greater importance of such feedback in terms of subsequent behavioral adjustment (Holroyd & Coles, 2002;Ridderinkhof, Ullsperger, Crone, & Nieuwenhuis, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, observing errors made by others also elicits a negative ERP, the observer ERN (oERN), whose topography and sources resemble the ERN but with delayed latencies (Bates, Patel, & Liddle, 2005;Carp, Halenar, Quandt, Sklar, & Compton, 2009;Koban, Pourtois, Vocat, & Vuilleumier, 2010;Miltner, Brauer, Hecht, Trippe, & Coles, 2004;van Schie, Mars, Coles, & Bekkering, 2004). Likewise, an observer FRN (oFRN) can be measured during the same time-window as the classical FRN (around 200-300 ms), but with smaller amplitudes for observers than agents of actions (Fukushima & Hiraki, 2009;Leng & Zhou, 2010;Yu & Zhou, 2006), possibly reflecting a decreased saliency of other-generated errors relative to one's own (Bellebaum, Kobza, Thiele, & Daum, 2010). Unlike the oERN (to the best of our knowledge), the neural sources of the oFRN have not been investigated yet.…”
Section: Effects Of Social Context and Predictive Relevance On Actionmentioning
confidence: 99%
“…However, other studies reported reduced FRN amplitudes in observation conditions (Bellebaum et al, 2010a;Fukushima and Hiraki, 2009;Itagaki and Katayama, 2008). It should be noted that in all previous studies examining feedback processing in an observation condition, the positive (e.g., gains or correct) or negative (e.g., losses or incorrect) feedback for the choice made on each trial represented only one player's outcome, either the participant's outcome or the observer's.…”
Section: Introductionmentioning
confidence: 92%
“…Monitoring others' actions may enable us to interact efficiently during joint action (Sebanz et al, 2006a;Vesper et al, 2010) and to learn by observation (Bellebaum et al, 2010;van Schie et al, 2004). Yet, an unresolved question concerns the processes that allow the attribution of error agency.…”
Section: Perception Of Social Agency During Action Monitoringmentioning
confidence: 99%